Design The Intersection of Upstream Search Data Accuracy With Downstream Traceability Fisheries Business in Indonesia - Soedrijanto, Angky; Istiqomah, Titis; Soeprijadi, Liliek (Hasanuddin University, 2021)
Fisheries business actors in Indonesia have different backgrounds in knowledge, education, social and psychology. This diversity creates obstacles to the application of traceability of Indonesian fishery products, so that they lack competitiveness in the international market. The research aims to find some simple schemes that are easily understood by Indonesian fisheries businesses to implement traceability extensively. Descriptive research method. Data were obtained from terrestrial surveys and interviews with business actors spread across various fishery centers in East Java, since 2015 until now. The results of the observations are arranged in a simple matrix to find the suitability of the behavior of the design business actors at each observation point. The results of the analysis show that: the commitment and consistency of the fisheries businessman is largely determined by the factors of knowledge, education, social, and psychology respectively. Knowledge is the best aspect of power to create the drafting of search data; because this aspect turns out to be 'forced' to 'understand' by all parties doing business. The design of the accuracy of the meeting point of upstream search data with downstream traceability can be realized through the dissemination of knowledge in a simple and applicable manner continuously, extending to all lines and implanted to consumers from an early age. The weak implementation of traceability in Indonesia is caused by the lack of consumer understanding of the importance of search data; which has a strong impact on suppliers to